Differences in nervous system properties, personality profiles, and mental reliability among basketball players of the Ukrainian deaflympic national team - Mazin, V.; Cherepiekhina, O.; Alibekov, A.; Bykov, V. (Journal of Physical Education and Sport, 2025)
Problem statement: Deaflympic athletes often face additional psychological and neurophysiological challenges due to communication barriers and sensory limitations. While the general psychophysiological traits of hearing impaired athletes have been explored, little is known about how participation in professional sports impacts the mental reliability, personality traits, and nervous system properties of Deaflympic athletes within the same national team. The importance of examining differences in nervous system characteristics, personality profiles, and mental reliability between basketball players of the Ukrainian Deaflympics national team who compete for professional clubs (n=6) and those who play only for the national team (n=5). Purpose: This study aimed to identify the differences in mental reliability, typological features of the nervous system, and personality profiles between Ukrainian Deaflympic basketball players who compete only for the national team and those who also play for professional clubs. Method: The study was performed in October 2024. The research instruments included the: "Mental Reliability of an "Athlete" scale, the "Typological Properties of the Nervous System" assessment, and "Cattell's 16-Factor Questionnaire". Data were collected online following individualized instructions provided to participants. Comparisons were made using Student's t-test. Results: The study revealed statistically significant differences (p < 0.05) between the groups on key psychodiagnostic scales. Athletes with additional experience in professional basketball clubs demonstrated higher scores in obstacle resistance, endurance under physical exertion, mobility of nervous processes, social boldness, self-reliance, and perfectionism. A slightly elevated tendency toward anxiety was also noted. No significant differences were observed on other scales. Conclusions: Basketball players of the Ukrainian Deaflympic national team with professional club experience demonstrate higher levels of mental reliability, stress endurance, and neurodynamic adaptability. They are characterized by greater self-regulation, social boldness, and autonomy, alongside a slightly increased tendency toward anxiety. These differences justify the inclusion of club-level athletes in national team selection and highlight the need for additional psychological support for those without professional experience. Further research is recommended across genders and Deaflympic sports to deepen understanding of psychophysiological profiles in this population.